Paranodal Axoglial Junctions, an Essential Component in Axonal Homeostasis - Ishibashi, Tomoko; Baba, Hiroko (Frontiers in Cell and Developmental Biology, 2022)
In vertebrates, a high density of voltage-gated Na+ channel at nodes of Ranvier and of voltage-gated K+ channel at juxtaparanodes is necessary for rapid propagation of action potential, that is, for saltatory conduction in myelinated axons. Myelin loops attach to the axonal membrane and form paranodal axoglial junctions (PNJs) at paranodes adjacent to nodes of Ranvier. There is growing evidence that the PNJs contribute to axonal homeostasis in addition to their roles as lateral fences that restrict the location of nodal axolemmal proteins for effective saltatory conduction. Perturbations of PNJs, as in specific PNJ protein knockouts as well as in myelin lipid deficient mice, result in internodal axonal alterations, even if their internodal myelin is preserved. Here we review studies showing that PNJs play crucial roles in the myelinated axonal homeostasis. The present evidence points to two functions in particular: (1) PNJs facilitate axonal transport of membranous organelles as well as cytoskeletal proteins; and (2) they regulate the axonal distribution of type 1 inositol 1,4,5-trisphosphate receptor (IP3R1) in cerebellar Purkinje axons. Myelinated axonal homeostasis depends among others on the state of PNJs, and consequently, a better understanding of this dependency may contribute to the clarification of CNS disease mechanisms and the development of novel therapies.